Nonlinear CO2 flux response to 7 years of experimentally induced permafrost thaw. (29th March 2017) - Mauritz, Marguerite; Bracho, Rosvel; Celis, Gerardo; Hutchings, Jack; Natali, Susan M.; Pegoraro, Elaine; Salmon, Verity G.; Schädel, Christina; Webb, Elizabeth E.; Schuur, Edward A. G.
Abstract: Rapid Arctic warming is expected to increase global greenhouse gas concentrations as permafrost thaw exposes immense stores of frozen carbon (C) to microbial decomposition. Permafrost thaw also stimulates plant growth, which could offset C loss. Using data from 7 years of experimental Air and Soil warming in moist acidic tundra, we show that Soil warming had a much stronger effect on CO2 flux than Air warming. Soil warming caused rapid permafrost thaw and increased ecosystem respiration (Reco ), gross primary productivity (GPP), and net summer CO2 storage (NEE). Over 7 years Reco, GPP, and NEE also increased in Control (i.e., ambient plots), but this change could be explained by slow thaw in Control areas. In the initial stages of thaw, R eco, GPP, and NEE increased linearly with thaw across all treatments, despite different rates of thaw. As thaw in Soil warming continued to increase linearly, ground surface subsidence created saturated microsites and suppressed R eco, GPP, and NEE. However R eco and GPP remained high in areas with large Eriophorum vaginatum biomass. In general NEE increased with thaw, but was more strongly correlated with plant biomass than thaw, indicating that higher Reco in deeply thawed areas during summer months was balanced by GPP. Summer CO2 flux across treatments fit a single quadratic relationship that captured the functional response of CO2 flux to thaw, water table depth, and plant biomass. These results demonstrate the importance of indirect thaw effects on CO2 flux: plant growth and water table dynamics. Nonsummer Reco models estimated that the area was an annual CO2 source during all years of observation. Nonsummer CO2 loss in warmer, more deeply thawed soils exceeded the increases in summer GPP, and thawed tundra was a net annual CO2 source. Abstract : In spring excess snow is removed from the Soil warming treatment to prevent delayed phenology and higher melt‐water input. Soil warming had a much stronger effect on CO2 flux than Air warming. Soil warming caused rapid permafrost thaw and increased ecosystem respiration (Reco ), gross primary productivity (GPP), and net summer CO2 storage (NEE). Summer CO2 flux across treatments could be explained by changes in thaw, water table depth and plant biomass. In the initial stages of thaw Reco, GPP, and NEE increased linearly with thaw and plant biomass. As thaw continued to progress in Soil warming, ground surface subsidence created saturated microsites and suppressed Reco and GPP, reducing summer CO2 sink strength in the most deeply thawed areas. Adding winter Reco losses to summer NEE showed that the tundra was a net annual CO2 source as Reco in warmed and in un‐warmed winter soils exceeded the summer CO2 sink.